1997
DOI: 10.1152/ajplung.1997.272.4.l673
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endothelial thiazine uptake: separation of cell surface reduction from intracellular reoxidation

Abstract: The objective of this study was to further evaluate the hypothesis that the accumulation of thiazine dyes, such as methylene blue, by cultured bovine pulmonary arterial endothelial cells involves reduction on the cell surface, followed by diffusion of the lipophilic reduced form of the dye into the cells and intracellular reoxidation to the relatively membrane-impermeant hydrophilic form. The specific question addressed was whether inhibition of methylene blue uptake by cyanide and azide is via inhibition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…However, the clinical use of MB has been hampered by its propensity for rapid chemical alteration when systemically applied: MB in the biological environment is usually converted by accepting electrons from NADH/NADPH, and unfortunately, the formed colorless leukomethylene blue (LMB) has negligible photodynamic activity [11][12][13]. Recent studies suggested the presence of a transmembrane thiazine dye reductase at the cell surface as the initial factor for MB reduction [14][15][16]. Once within the cells, MB also can be reduced via NADH/NADPH dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical use of MB has been hampered by its propensity for rapid chemical alteration when systemically applied: MB in the biological environment is usually converted by accepting electrons from NADH/NADPH, and unfortunately, the formed colorless leukomethylene blue (LMB) has negligible photodynamic activity [11][12][13]. Recent studies suggested the presence of a transmembrane thiazine dye reductase at the cell surface as the initial factor for MB reduction [14][15][16]. Once within the cells, MB also can be reduced via NADH/NADPH dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, inhibitors are used to provide discriminating data relevant to these processes, and kinetic modeling is used to interpret such data and obtain values for kinetic parameters descriptive of the individual processes involved. Using this overall strategy, we have studied the impact of pulmonary endothelial cells on a variety of redox-active and other substances (4,12,13,38,40,41). The studies have revealed the wide range of pulmonary endothelial redox enzymes and other processes capable of influencing the metabolism, redox status, and disposition of compounds carried in the blood.…”
mentioning
confidence: 99%
“…It was proposed that MB ϩ freely diffuses across the erythrocyte membrane and is rapidly reduced to MBH, which is then trapped in the cell (36). On the basis of their studies in pulmonary arterial endothelial cells, however, Merker and colleagues (3,26,27,30) concluded that MB ϩ is reduced at the exofacial cell surface. The resulting MBH diffuses into the cell, where it is oxidized to MB ϩ , which is then trapped in the cell.…”
mentioning
confidence: 99%